Concise Xanthine Synthesis through a Double‐Amidination Reaction of a 6‐Chlorouracil with Amidines using Base‐Metal Catalysis. Issue 3 (12th January 2017) - Morel, Bénédicte; Franck, Philippe; Bidange, Johan; Sergeyev, Sergey; Smith, Dan A.; Moseley, Jonathan D.; Maes, Bert U. W.
Abstract: A new and concise route towards xanthines through a double‐amidination reaction is described; consecutive intermolecular C−Cl and intramolecular oxidative C−H amidination. N ‐uracil amidines are obtained through SN AE on a 6‐chlorouracil with amidines. Direct Cu‐catalyzed oxidative C−H amidination on these N ‐uracil amidines yields polysubstituted xanthines. Sustainable oxidants, t Bu2 O2 or O2, can be used in this oxidase‐type reaction. The protocol allows for the introduction of N 1, N 3, N 7, and C 8 substituents during the xanthine‐scaffold construction, thus avoiding post‐functionalization steps. Both 6‐chlorouracils and amidines are readily available commercially or through synthesis. Abstract : Simple xanthine synthesis : A new two‐step approach for the synthesis of polysubstituted xanthines is described. Starting from simple building blocks, 6‐chlorouracil and amidines, a SN AE amidination reaction is developed, followed by a base‐metal‐catalyzed intramolecular direct oxidative amidination. O2 or t Bu2 O2 can be used as oxidant for the latter transformation.